PELAKSANAAN PEMBELAJARAN DARING DALAM PROSES PENCAPAIAN PENDIDIKAN BERKUALITAS PADA ERA REVOLUSI INDUSTRI 4.0 DI SD CENDEKIA ISLAMIC SCHOOL SERANG-BANTEN - Diki Akmal Wildan; Indhira Asih Vivi Yandari; Istinganatul Ngulwiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the implementation of online learning to achieve qualified education in the era of the industrial revolution 4.0 at SD Cendekia Islamic School. It also includes the description process of the implementation of online learning conducted by teachers and the result description achieved by students during online learning. Online learning is applied based on Kemendikbud’s Circular Letter No. 4 in 2O2O regarding the Implementation of Education Policiesthat one of which states that learning from home during the emergency spread pandemic of Corona Virus Disease (COVID-19) is applied by following the protocol rules for COVID-19, which requires to make learning at home. Hence, teachers and students should follow online learning. Online learning is learning that is implemented through technology as media. Yet, lessons learned from the implementation of online learning are the orientation of teaching and learning quality in the industrial revolution 4.0. In this era, technological developments are developing rapidly so itproduces a shift of paradigm on how to make complex and varied learning from humans. It, of course, is indicated that students should understand and be able to develop the use of technology in daily life, especially in online learning. And it is also affiliated on qualified education achievement with the abilities and skills that students must have in this digital era, industrial revolution 4.0. The qualities of education are to apply character education, literacy, and 4C (critical thinking, creativity, communication, and collaboration). The approach conducted in this research is a qualitative approach with a descriptive method. During the research process, the researcher tried to describe all events and phenomena that occurred, especially events that are related to the objectives, and only focused on the research topics.